Immunoglobulin Y for Potential Diagnostic and Therapeutic Applications in Infectious Diseases - Lee, Lucia; Samardzic, Kate; Wallach, Michael; Frumkin, Lyn R.; Mochly-Rosen, Daria (Frontiers in Immunology, 2021)
Antiviral, antibacterial, and antiparasitic drugs and vaccines are essential to maintaining the health of humans and animals. Yet, their production can be slow and expensive, and efficacy lost once pathogens mount resistance. Chicken immunoglobulin Y (IgY) is a highly conserved homolog of human immunoglobulin G (IgG) that has shown benefits and a favorable safety profile, primarily in animal models of human infectious diseases. IgY is fast-acting, easy to produce, and low cost. IgY antibodies can readily be generated in large quantities with minimal environmental harm or infrastructure investment by using egg-laying hens. We summarize a variety of IgY uses, focusing on their potential for the prevention and treatment of human and animal infections.